The Effect of Health Community Behavior (PHBS), Health Service Quality to Diare’s Disease in Sub-Division Karang Jaya Palembang Sub-District - Iman Suwono; MT Kamaluddin; Sriati Sriati; Dwi Putro Priadi (Program Pascasarjana Universitas Sriwijaya, 2018)
AbstractThe aims of this study were to analyze the Effect of Healthy Living Community Behavior (PHBS), Quality of Health Service against Overcoming Diarrhea Disease in Sub-division Karang Jaya Palembang. The type of research used in this study was analytical research. This research was conducted in Palembang City selected area of Karang Jaya Sub-district Gandus District. The study was conducted in May 2016 to June 2017. The samples of research were people affected by diarrhea in 2017 as many as 95 people. Method’s of data analysis using logistic regression. Result showed that the PHBS coefficient with odds ratio-0.760 (1.561-0.370) with significance of 0.045 less than the 0.05 significance level (α). This means that hypothesis one (H1) was accepted if the variable quality of health service, constant then every increase PHBS effect on the occurrence of diarrhea. The better PHBS will decrease the incidences of diarrhea. Coefficient of health service quality with odds ratio 1.598 (3.217-0.74) with significant equal to 0.009 less than level of significant (α) 0.05. This means that hypothesis two (H2) is accepted if the variable PHBS, constant then the quality of health services affect the occurrence of diarrhea. The better quality of health care will reduce the incidence of diarrhea Keywords: PHBS, quality of service, health, diarrhea